Common Entrapment Neuropathies - Malek, Elia; Salameh, Johnny S. (Seminars in Neurology, 2019)
Entrapment neuropathies are defined as compression of peripheral nerves due to known or unknown causes. The high incidence and variety of presentations require a comprehensive knowledge of these conditions, especially in neurology and orthopedic surgery clinical practices. Detailed knowledge of topographic anatomy, clinical manifestations, and appropriate use of electrophysiological studies with selective addition of neuromuscular ultrasonography are needed to establish an early and accurate diagnosis to advice patients and provide them with a comprehensive treatment plan. In this article, we discuss the most common forms of entrapment neuropathies in the upper and lower extremities.
Keywords: entrapment neuropathies; compression neuropathies; mononeuropathies